Republic of Belarus : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Payment Systems, and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews key findings of Belarus's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Banking Supervision, Payment Systems, and Anti-Money Laundering and Combating the Financing of Terrorism. Although significant progress has been made in upgrading the financial system's technical infrastructure and the regulatory and supervisory framework, financial sector structural reform has been slow overall. The centralized approach to economic management continues to dominate the financial system. The major banks, which are with one exception government owned or controlled, are frequently requested to lend to priority enterprises and sectors.